The Concept of Ijmā’ in the Modern Age with particular reference to Muhammad ‘abduh’s Theory - Khoiruddin Nasution (Al-Jami'ah Research Centre, 1994)
The Qur'ān and the Sunna of the Prophet are the main sources of Islamic jurisprudence, from and through which the Islamic laws are derived. The Sunni jurists agree that ijma' is the third source of Islamic law after the Qur'ān and the Sunna of the Prophet. Even though some modern scholars, such as Snouck Hurgronje argues that ijma' as a method and principle rather than its contents which are regarded as authoritative, not infallible. Islamic jurisprudence deals with acts of worship ('ibādat), such as praying, fasting, zakat etc. As well as with mu'amalat such legal transaction, family law, public activity, international commerce, international realtions and so forth. After the death of the Prophet, to whom the Qur'ān was revealed and from whom the Sunna came, Ijma' and ijtihad, became imperative, since it was only through them that new problems, which the Qur'ān and the Sunna of the Prophet did not adequately explain could be solved.